Quantitative evaluation of soil anti-erodibility in the fluctuation zones of rooted soil in a large reservoir, southwest of China - Pengcheng Wang; Xinghan Niu; Henglin Xiao; Gaoliang Tao; Zexi Song (PLoS ONE, 2026)
The quantitative analysis of key factors influencing the erosion resistance characteristics of colluvial zone soil is a prerequisite for accurately assessing the erosion resistance ability of the soil. Therefore, this study focuses on the reservoir erosion zone of the Guanyinyan Reservoir area in the Jinsha River Basin, which is a large hydropower station. The physicochemical characteristics of the colluvial zone soil (bulk density, moisture content, total porosity, soil texture, pH, organic matter content, and aggregate stability) as well as erosion resistance capabilities (soil erodibility factor K and shear strength) with variations in water level elevation (low, middle, and high elevations) were analyzed. This study quantitatively evaluated the relative importance of soil physicochemical characteristics to soil erosion resistance, identified key influencing factors, and subsequently constructed a comprehensive evaluation model for soil erosion resistance. The research results indicate that: 1) Redundancy analysis (RDA) and correlation analysis reveal that the soil erodibility factor K is significantly negatively correlated (P < 0.01) with total porosity, sand content, organic matter, mean weight diameter (MWD), geometric mean diameter (GMD), water-stable aggregates larger than 0.25 mm (WSA 0.25 ), and dry-sieved aggregates larger than 0.25 mm (DSA 0.25 ). It is also significantly positively correlated (P < 0.01) with percentage of aggregate destruction for aggregates larger than 0.25 mm (PAD), the silt content, and the clay content. However, it was not significantly correlated with the bulk density, moisture content, or pH. The soil shear strength is significantly negatively correlated (P < 0.05) with the moisture content, clay content, and soil erodibility factor K. The shear soil strength is significantly positively correlated (P < 0.05) with the MWD and DSA 0.25 . 2) Fourteen erosion resistance indicators of the colluvial zone soil in the Guanyinyan Reservoir area were selected, and a comprehensive evaluation model for soil erosion resistance was established on the basis of Principal Component Analysis (PCA). 3) The Comprehensive Soil Erosion Index (CSEI) in the Jinping Gaunyinyan Reservoir erosion zone varies between 0.082 and 0.942 with changes in water level elevation. For different elevations, the comprehensive soil erosion indices are as follows: high (root zone soil) <middle (root zone soil) <high (un-rooted zone soil) <middle (un-rooted zone soil) <low (root zone soil) <low (un-rooted zone soil). At the same water level elevation, with decreasing flooding time, the CSEI of the un-rooted zone soil in the erosion zone increased by 41.03%, 96.91%, and 353.13% compared with that of the root zone soil. In the reservoir erosion zone of the Guanyinyan Reservoir area, the overall Comprehensive Soil Erosion Index (CSEI) decreases with increasing water level elevation. At the same elevation, the CSEI of the un-rooted zone soil is significantly greater than that of the root zone soil, and this difference further increases with decreasing flooding time.